Mengurai Perkembangan Rantai Ilmu Pengetahuan; Sebuah Tinjauan Filsafat Ilmu - Abd Ghofur (Jurnal Penelitian Pendidikan, 2015)
This article attempts to reveal the science development from time to time. Beingits wider field and scientific study, the authors focused only on the development ofscience which had been discovered by earlier scientists from generation to generation.Where pioneering personage of his day had been succesful to carve the milestones of atheory to be utilized as a study and produce a variety of science becoming increasinglysophisticated technology in this era. The development of science in this period can notbe separated away from the role of philosophy of science. So the researchers probedthe initial data from the philosophy of science that had been developed by the Greekphilosophers. Many experts were debating the onset of science. Some stated that scienceexisted since pre-history, in which the time, according to the experts, was declared as theperiod of pre-history (not familiar with writing).